Erbium laser for ceramic restoration retrieval - Suliman, Sama A. (fi=Turun yliopisto|en=University of Turku|, 2026)
Conventional removal of all-ceramic dental restorations using rotary instruments can be time-consuming technique-sensitive and may damage both the restoration and underlying tooth or implant abutment. With the increasing clinical use of high strength ceramics such as yttria-stabilized zirconia (Y-TZP) and lithium disilicate glass ceramics, there is a growing need for non-invasive retrieval techniques that preserve both the restoration and supporting structures. Erbium-doped yttrium aluminum garnet (Er:YAG) lasers have emerged as a potential solution, offering selective cement ablation while minimizing harm to surrounding tissues. This PhD research aimed to comprehensively evaluate the efficiency and effects of Er:YAG laser-assisted debonding of contemporary ceramic restorations across three experimental studies. The first study investigated the impact of yttria concentration in monolithic zirconia (3Y-TZP, 4Y-TZP, 5Y-TZP) and lithium disilicate on laser debonding time. The second study assessed the influence of adhesive bonding strategy used with resin cements, comparing two-bottle and one bottle adhesive systems on laser debonding performance. The third study focused on how Er:YAG irradiation affects key optical and mechanical properties of these ceramics, including color stability (ΔE00), translucency parameter (TP), biaxial flexural strength, and surface roughness. Results demonstrated that debonding time decreased with increased yttria content in zirconia and that lithium disilicate required the shortest retrieval time. No statistically significant differences were observed in debonding time between the two resin cement systems. Er:YAG irradiation caused material-specific changes in color and flexural strength but did not adversely affect surface roughness or translucency in most cases. In conclusion, Er:YAG laser-assisted removal offers a safe and efficient approach for retrieving ceramic restorations, with minimal alterations to their structural integrity. These findings support the clinical viability of reusing restorations post-debonding and provide a scientific foundation for minimally invasive, laser-guided prosthodontic treatment protocols.